2012
DOI: 10.1111/j.1365-2621.2012.03146.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, technological properties and genetic relationships among twenty cowpea landraces cultivated in West Africa

Abstract: The genetic relationships among twenty phenotypically different cowpea landraces were unravelled regarding their suitability for preparing West African dishes. Amplified fragment length polymorphism classified unpigmented landraces (UPs) as highly similar (65%, one cluster), contrary to pigmented landraces (PLs, three clusters). UPs contained, in g kg À1 d.w., less fibre (24) and phenolics (3) than PLs (56 and 8, respectively) but had bigger seeds (200 g d.w. for 1000 seeds) and lower water absorption capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
2
9
1
Order By: Relevance
“…The range of values we observed for iron (4.9–8.2 mg/100 g d.w) and zinc (2.7–4.1 mg/100 g d.w) were somewhat lower than the 5.6–10.4 mg/100 g d.w and 3.7–5.4 mg/100 g d.w respectively observed among cowpea landraces in Benin [37]. Based on iron and zinc concentrations the results suggest that zanzi zee could be promoted as the most suitable landrace with the potential to improve iron intake.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The range of values we observed for iron (4.9–8.2 mg/100 g d.w) and zinc (2.7–4.1 mg/100 g d.w) were somewhat lower than the 5.6–10.4 mg/100 g d.w and 3.7–5.4 mg/100 g d.w respectively observed among cowpea landraces in Benin [37]. Based on iron and zinc concentrations the results suggest that zanzi zee could be promoted as the most suitable landrace with the potential to improve iron intake.…”
Section: Discussioncontrasting
confidence: 79%
“…Based on iron and zinc concentrations the results suggest that zanzi zee could be promoted as the most suitable landrace with the potential to improve iron intake. However, the phytate and polyphenol concentrations of the landraces were high but within range of values reported by Madode et al [37]. Iron and zinc absorption are partly influenced by phytate and polyphenol concentration [35], [38].…”
Section: Discussionsupporting
confidence: 67%
“…Potassium content of samples varied from 17074.00 to 24078.00 mg kg -1 and significantly higher mean values were recorded in genotypes 98K-5301 and ITOOK-1060 compared to the rest of the genotypes.The mean calcium content ranged between 2236.70 and 8677.70 mg kg -1 in genotype 98K-5301 and genotype Pan311, respectively. In a study of 20 cowpea landraces in Benin, Madode et al (2012) reported calcium content variation of 700-1400 mg kg -1 , while a range of 56-104 mg kg -1 and 37-54 mg kg -1 are reported for iron and zinc respectively. Similarly, the highest mean phosphorus content was recorded in genotype 98K-5301 with the concentration amount of (5375.30 mg kg -1 ), while the lowest mean value was obtained in genotypes IT845-2246 (3834.30 mg kg -1 ).…”
Section: Analysis Of Variance For Nutritional Valuesmentioning
confidence: 99%
“…However, the highest concentration was recorded in genotype TVU-14196 and was found to be the best source of iron among the genotypes, but far lower than the values reported by Ano and Ubonchi (2008) in Nigeria. According to Madode et al (2012), the differences between the various studies could be attributed to varietal differences, but are more likely to result from differences in soil fertility. The variation of both micronutrients and macronutrients observed in the current study might be attributed to the differential ability of the genotypes to absorb the mineral elements from the soil and transport them into the plant system (Shegro et al, 2012).…”
Section: Analysis Of Variance For Nutritional Valuesmentioning
confidence: 99%
“…In Nigeria, they are also used in preparing other food products such as fried cowpea cakes, bean soup, and a steamed popular delicacy called moinmoin. Nutritionally, cowpea seeds contain 61%-66% carbohydrates, 24%-25% proteins, and 1.0%-2.0% lipids (Bressoni, 1985;Madode, Linnemann, Nout, Vosman, & Hounhouigan, 2012).…”
mentioning
confidence: 99%